2007
DOI: 10.1158/1055-9965.epi-07-0324
|View full text |Cite
|
Sign up to set email alerts
|

Joint Effects of Dietary Trace Metals and DNA Repair Capacity in Lung Cancer Risk

Abstract: In a large case-control study, we previously reported that dietary intakes of zinc (Zn) and copper (Cu), but not selenium (Se), were inversely associated with lung cancer risk. Because Zn, Cu, Se, iron (Fe), and calcium (Ca) are important for maintaining DNA stability, we examined their associations with DNA repair capacity (DRC) measured by the lymphocyte host-cell reactivation assay in 1,139 cases and 1,210 of the controls. Dietary intake was reported in a food frequency questionnaire. In multivariate analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 19 publications
4
18
2
Order By: Relevance
“…It has been reported that selenium supplementation, in a form mainly composed of selenomethionine, reduces risk of prostate, colon, and lung cancer [Clark et al, 1996]. Another study documented an inverse relationship between risk of lung cancer and dietary intakes of zinc and copper, but not selenium [Mahabir et al, 2007].…”
Section: Inorganic Nutrientsmentioning
confidence: 99%
“…It has been reported that selenium supplementation, in a form mainly composed of selenomethionine, reduces risk of prostate, colon, and lung cancer [Clark et al, 1996]. Another study documented an inverse relationship between risk of lung cancer and dietary intakes of zinc and copper, but not selenium [Mahabir et al, 2007].…”
Section: Inorganic Nutrientsmentioning
confidence: 99%
“…Trace elements are essential micronutrients that are involved in many important biological processes such as functioning as cofactors for the activity of the antioxidant enzymes, cell division, and differentiation [1,2]. Imbalances in levels of trace elements could adversely affect human health.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to reactive oxygen species (ROS) can lead to direct DNA damage, mutation, and carcinogenesis [6,7]. Previous studies have reported alterations in the concentrations of serum or neoplastic tissue trace elements in various carcinomas including breast, bladder, gastric, gallbladder, and lung cancers [1,[8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…They are cofactors for enzymes including Cu-Zn superoxide dismutase and DNA repair proteins, and also maintain DNA integrity [6,7]. Disturbed zinc and copper homeostasis has been associated with many types of cancer, such as gastrointestinal, lung, breast, and those of the female reproductive organs [8,9,10].…”
Section: Introductionmentioning
confidence: 99%